‘Joy, not sorrow’: Men's perspectives on gender, violence, and cash transfers targeted to women in northern Ghana - Pereira, Audrey; Akaligaung, Akalpa J.; Aborigo, Raymond; Peterman, Amber; Palermo, Tia; Barrington, Clare (Elsevier, 2023)
Evidence indicates that cash transfers can decrease intimate partner violence (IPV) against women, although most research has focused on women's perspectives and experiences, with less attention to men. We analyzed data from four focus group discussions with male partners of women who participated in the Ghana Livelihood Empowerment Against Poverty (LEAP) 1000 cash transfer program. We elicited men's perceptions of poverty, relationship dynamics, IPV and cash transfers targeted to their wives using thematic analysis. Men largely viewed the effects of the cash transfer as positive – they felt decreased provider role strain when women used the cash to cover household expenses such as food and school fees. Men also indicated that they felt respected when women used the cash to cover sudden expenses, such as funeral costs, thus preventing the need to borrow from community members and exposing their inability to fulfill provider roles. These feelings of relief and respect helped improve men's overall wellbeing, their marital relationships and reduced the potential for IPV. Despite these positive results, men revealed that they still expected to be informed and consulted about the transfer and its expenditure, and felt disrespected when women did not do so, thus heightening the potential for household conflict. Further research and innovation in programming is needed to integrate gender transformative strategies into cash transfer programs, explicitly aimed at changing gender norms to enhance and sustain beneficial impacts on gender relations and IPV.